156k views
5 votes
If T: (x, y) = (x-3, y + 2), then 7-1: (x,y) →

User Smerlin
by
4.9k points

1 Answer

1 vote

Answer:

(4,1)

Explanation:

The question is

Find the image of the given point

we know that

The rule of the translation is

(x,y) → (x-3,y+2)

That means ---> The translation is 3 units at left and 2 units up

we have the point (7,-1)

Apply the rule of the translation to the point (7,-1) (pre-image) to obtain the image

(7,-1) → (7-3,-1+2)

(7,-1) → (4,1)

User Kosta Kontos
by
5.1k points